Antioxidant activity, phytochemical analysis and total polyphenolics content of essential oil, methanol extract and methanol fractions from Commelina nudiflora - Muhammad Dawood Shah; Mohammad Iqbal (2018)
Objective: In the present study, the essential oil, methanol extract, and methanol fractions (n-hexane, chloroform, ethyl acetate, and n-butanol) obtained from Commelina nudiflora were investigated for the free radical scavenging effects and phytochemical analysis. Methods: The antioxidative effect of the essential oil, methanol extracts and methanol fractions were evaluated using 2, 2 diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. Total phenolic and flavonoid contents were determined using Folin-Ciocalteau and aluminium chloride reagents respectively. The phytochemical analyses of the essential oil, methanol extracts and methanol fractions were performed by gas chromatography and mass spectrometry (GCMS). Results: The antioxidant, total phenolic and total flavonoid contents of butanol, ethyl acetate and chloroform fractions were higher followed by methanol extract, hexane fraction and essential oil. Phytochemical analysis indicated the presence of alkaloid, saponin, steroid, phytosterols, triterpenoids and tannins etc. The identified bioactive constituents of essential oil, methanol extract and methanol fractions ofC. nudiflorawere indole, 2-methoxy-4-vinylphenol, 2-pentadecanone, 6,10,14-trimethyl, phenol, benzyl alcohol, eugenol, phenol, 2, 4-bis (1,1-dimethylethyl), hexadecanoic acid, ethyl ester (palmitic acid ester), n-hexadecanoic acid (palmitic acid), 9, 12-octadecadienoic acid, (linoleic acid) and phytol. All identified bioactive compounds and their derivatives were generally reported with antimicrobial, antioxidant, anti-inflammatory and antitumor properties. Conclusion: The obtained data suggest that the essential oil, methanol extract and methanol fractions of C. nudiflorapossess remarkable antioxidant activities and vital phytochemicals. Thus the plant cKeywords: Commelina nudiflora, Phytochemical compounds, Antioxidants, Methanol extract